First report of Enterobacter cloacae causing soft rot disease on potato in Iraq - Dhahir, H.R; Ahmed, F. A. (Journal of Kerbala for Agricultural Sciences, 2023)
Potato is an economically important crop, considered the fourth major crop worldwide. However, it has been exposed to many pathogens that cause significant yield loss. Bacterial soft rot diseases caused by Enterobacter cloacae is one of the most devastating on potatoes. The pathogenicity test conducted on several bacterial isolates isolated from potato tubers showing soft rot showed that 4 of these isolates could cause disease in potatoes. The size of damaged segments of potato slices ranged between 5.50 and 7.93 cm. The isolate H.B1 caused the most significant damage of 7.93 cm of tuber slices. Furthermore, the inoculation was carried out on 5-week-old potato plants. The bacteria were added through irrigation water at a concentration of 1x106 CPU. After 20 days of infection, symptoms of wilting and yellowing were observed on the inoculated plants. The biochemical tests displayed that the bacteria are negative for Gram stain and positive for the catalase test, gelatin liquefaction, starch hydrolysis and facultative aerobic. The nucleotide sequence analysis of 16 S marker results exhibited a similarity rate of 94%. Thus, isolate H.B1 was recorded in NCBI under registration number OP936020.